Strategi Efektif Penggunaan Media Sosial (TIKTOK) dalam Pembelajaran Agama di Era Digital - Baharudin Ihsan; A. Anzilna Munzalan. M; Laksa Rizal Putra. W; David Yusuf. A; M. Helmi; Nurudin Nurudin (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2024)
This journal aims to analyze effective strategies for using social media (Tok Tok) in religious learning in the digital era. In today's digital era, social media has become an important platform for individuals to get information and interact online. This can also be used as a means of learning about religion through content about religion on the platform (Tik Tok). This qualitative research analyzes data using a library observation methodology to understand effective strategies for using TikTok as a means of religious learning in the digital era. This research includes collecting journal references, analyzing them, and discussing important points. This research is descriptive in nature and focuses on the influence of religious content on students' understanding of religion on TikTok. This research involved 50 students from various academic levels and departments. Data analysis is carried out throughout the research, in contrast to quantitative research where data analysis is carried out at the end of the research.